2014
DOI: 10.4103/0972-9941.124454
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic hepatectomy: Advances in laparoscopic liver surgery

Abstract: BACKGROUND:Laparoscopic liver surgery is now an established practice in many institutions. It is a safe and feasible approach in experienced hands. Single incision laparoscopic surgery (SILS) has been performed for cholecystectomies, nephrectomies, splenectomies and obesity surgery. However, the use of SILS in liver surgery has been rarely reported. We report our initial experience in seven patients on single incision laparoscopic hepatectomy (SILH).PATIENTS AND METHODS:From October 2010 to September 2012, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 23 publications
(28 reference statements)
0
21
0
Order By: Relevance
“…Easily accessible, superficial lesions in segments II, III, IV, V, and VIII [20, 28] are preferable, even though bigger or more technically challenging resections for less favourably located tumours have been described with increased experience in the technique (Table 1). With regard to the size of the lesions, most groups adopted a cut-off of <2.5–5 cm in diameter for malignant and <10 cm for benign tumours [12, 14, 2022, 27, 28, 31]. Resection of larger malignant lesions has also been described [15, 20, 22]; however the potential extension of the incision for extraction of large specimen defeats the purpose of SILS [27].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Easily accessible, superficial lesions in segments II, III, IV, V, and VIII [20, 28] are preferable, even though bigger or more technically challenging resections for less favourably located tumours have been described with increased experience in the technique (Table 1). With regard to the size of the lesions, most groups adopted a cut-off of <2.5–5 cm in diameter for malignant and <10 cm for benign tumours [12, 14, 2022, 27, 28, 31]. Resection of larger malignant lesions has also been described [15, 20, 22]; however the potential extension of the incision for extraction of large specimen defeats the purpose of SILS [27].…”
Section: Resultsmentioning
confidence: 99%
“…Even though liver resections in cirrhotics may pose a greater challenge, SILS has also been described in this group of patients. Nonetheless, most cases were limited to early Child's A stage patients [12, 20, 28, 31], with only 3 cases reported in Child's B [12, 31] and 1 case in a Child's C patient [31]. The small number of reported SILS liver resections in the literature precludes direct comparison with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The literature research revealed 343 articles, of which 16 [ 17 ], [ 18 ], [ 19 ], [ 20 ], [ 21 ], [ 22 ], [ 23 ], [ 24 ], [ 25 ], [ 26 ], [ 27 ], [ 28 ], [ 29 ], [ 30 ], [ 31 ], [ 32 ] met the inclusion criteria. One study [ 26 ] had to be excluded since the same patients were reported in another publication [ 27 ] (Figure 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although we note that the authors have professed high skill levels in performance of gastrectomy with D 2 lymphadenectomy, sans complications,[8] certain thoughts merit deep introspection:…”
mentioning
confidence: 99%
“…[12] Interestingly, in the present article, only 42% of patients who underwent ERAS were Stage III suggesting that over 50% cases presenting to a government hospital were in Stages I and II. [8]Given the evolving concept of multidisciplinary approach to management of gastric cancer, the incorporation of data on neoadjuvant or adjuvant treatment would perhaps give us a comprehensive view of oncological outcomes, which should be at the centre of any study in oncology. [12]…”
mentioning
confidence: 99%